2022
DOI: 10.5624/isd.20210231
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of maturation stages and the accuracy of age estimation methods in a Turkish population: A comparative study

Abstract: Purpose This study assessed the associations between chronological age, dental maturation (DM), cervical vertebrae maturation (CVM), and hand-wrist maturation (HWM) in individuals aged 9-19 years. In addition, this study aimed to derive practical methods to evaluate the skeletal age using DM, CVM, or HWM for orthodontic, medical, and forensic purposes and to compare which of these 3 developmental parameters is more accurate for estimating the age of individuals in a Turkish population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 34 publications
0
14
0
3
Order By: Relevance
“…for title and abstract. Out of these, we included 25 papers for full-text screening [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Six articles not respecting eligibility criteria were excluded by the systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…for title and abstract. Out of these, we included 25 papers for full-text screening [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Six articles not respecting eligibility criteria were excluded by the systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Camacho-Basallo et al [23] reported significant correlations (P < 0.001) between the two methods with the exception of the first molars that showed a low significant correlation in female (CC = 0.263; P < 0.05) and not significant correlation in male (CC = 0.187; P > 0.05). Magat et al [32] evaluated only third molars and found only a moderate correlation between the dental developmental stages of third mandibular molars and the start of PGS (P < 0.05) in both males and females.…”
Section: Correlation Between Fishman and Demirjian Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…No to nije točan pokazatelj stupnja djetetova razvoja s obzirom na to da stupanj rasta i razvoja varira od osobe do osobe (3,4). Zato su u literaturi opisane različite metode, uključujući procjenu dentalne i skeletne dobi koja se može izračunati iz panoramskih, kefalometrijskih i običnih rendgenskih snimaka šake kao i slika kompjutorizirane tomografije s konusnom zrakom (CBCT) (5,6).…”
Section: Uvodunclassified
“…However, it is not an accurate indicator of the stage of development of the child, since the stage of growth-development varies from one individual to another (3,4). Therefore a variety of methods, including dental and skeletal age estimation which can be calculated from panoramic, cephalometric, and hand-wrist plain radiographs as well as cone-beam computed tomography (CBCT) images have been described in the literature (5,6).…”
Section: Introductionmentioning
confidence: 99%